Gambaran Pengetahuan Wus Tentang Pap Smear Di Bidan Nurul Intan S, Amd.Keb Kabupaten Pamekasan - Rohimah (Akademi Kebidanan Aifa Husada Madura, 2019)
A Pap smear is a method for examining cells taken from the cervix and then examined under a microscope to see the changes that occur in these cells. One of the efforts taken was by examining smear (Pap smear). Based on pre-survey results in the village of Pagantenan through short interviews with 10 mothers on April 11, 2016, 3 people found out about Pap Smear and the remaining 7 people did not know about Pap Smear. This study aims to determine the WUS Knowledge Description of Pap Smear in Intan S Nurul Midwife, Amd. Keb Pamekasan Regency. This type of research is descriptive. The population is all WUS in the Polindes area, Midwife Nurul Intan S, Amd. Keb. With a sample size of 300 people. The sampling technique uses non-probability sampling technique with purposive sampling where the sampling is purposively based on the characteristics or characteristics of the population that have been previously known. The technique of collecting data through questionnaires with closed question forms, after the data collected is analyzed by the formula presented in the frequency distribution table. The results showed that the description of WUS's knowledge of Pap Smear in the Polindes Region of Intan S Midwife S, Amd. Keb, Pamekasan Regency can be interpreted, that is, almost all respondents have less knowledge. Based on the above phenomenon, it is necessary to hold counseling (KIE) to the community. Therefore, the participation of health workers to increase knowledge and information about reproductive health and provide counseling to women is very important in addition to meeting health professionals such as health seminars and posyandu. For women who have been married for a long time and have given birth, it is advisable to diligently carry out early detection of cervical cancer (Pap Smear) so that it can prevent cervical cancer.